Are diaphyseal clavicular fractures still treated traditionally in a non-surgical way? - Pedro José Labronici; Fernando Claudino dos Santos Filho; Tales Bregalda Reis; Robinson Esteves Santos Pires; Adriano Fernando Mendes Junior; Kodi Edson Kojima (Revista Brasileira de Ortopedia)
ABSTRACT OBJECTIVE: To evaluate the decision of orthopedics surgeons regarding which cases they would indicate surgery or non-surgical treatment. METHODS: 20 images of radiographs with fracture in the middle third of the collar bone (AO/OTA 15-B) in anteroposterior view were analyzed, and divided into four groups: group 1 - fracture type AO/OTA 15-B1 without displacement; group 2 - fracture type AO/OTA 15-B1 with displacement; group 3 - fracture type AO/OTA 15-B2; group 4 - fracture type AO/OTA 15-B3. The evaluator was requested to indicate the choice of treatment, surgical or non-surgical. RESULTS: There was no strong correlation between the amount of surgical indications and the working experience or age of the medical evaluator. It was observed that the average of surgical indications in the total sample was 52%. When indications were studied in different areas of Brazil, there was no significant difference among them. No pattern for the Brazilian regions studied was observed in the case analysis. Even within a group (cases of the same complexity), no specific pattern of surgical indication was observed. CONCLUSION: No association between surgical indication and the length of professional experience was found. The Southern and Southeastern regions were those that most recommended surgeries in groups 2, 3, and 4. In no region the same level of surgical indication for cases of the same complexity rate was kept.